Osteotomy combined with lateral ligament reconstruction in treating osteochondral lesion in patients with talar injury and varus ankle. Issue 12 (26th March 2021) - Hu, Mu; Xu, Xiang-Yang
Abstract : Abstract: This study aimed to investigate the therapeutic effects of osteotomy combined with lateral ligament reconstruction on the osteochondral lesion of patients with talar injuries and varus ankles. Seventy five patients with talar injuries and varus ankles who received osteotomy combined with lateral ligament reconstruction for the osteochondral lesions from June 2008 to December 2014 were retrospectively reviewed. Patients were followed up for 32.4 ± 15.3 months after surgeries, and the AOFAS-AH score, VAS score and SF36 score were determined preoperatively and postoperatively. The iconographic data were compared preoperatively and postoperatively, including tibial anterior surface angle (TAS), TTS, TT, and tibial lateral surface angle (TLS) angles. After surgeries, the AOFAS-AF score increased from 43.2 ± 8.1 to 82.1 ± 5.6, the VAS score decreased from 6.9 ± 2.3 to 1.8 ± 1.5, and the SF36 score increased from 48.7 ± 9.4 to 83.5 ± 6.2. TAS increased from 83.3 ± 5.1 to 90.3 ± 6.1, TTS increased from 70.3 ± 6.1 to 82.5 ± 5.4, TT decreased from 12.9 ± 6.1 to 6.9 ± 5.7, and TLS increased from 76.5 ± 4.1 to 81.2 ± 3.3 ( P  < .05). Osteotomy combined with lateral ligament reconstruction is effective for the treatment of talar osteochondral lesion with varus ankle, which could relieve the arthritic symptoms induced by cartilage lesions. By correcting the force line on lower limbs and metapedes with osteotomy completely, the treatments on talar osteochondral lesion and lateral ligament reconstruction are the critical factors with better results.